Quantitative microscopy based on single-molecule fluorescence. (August 2017) - Jung, Seung-Ryoung; Fujimoto, Bryant S; Chiu, Daniel T
Highlights: Single-molecule based statistical deconvolution quantitative microscopy. Single-molecule localization microscopy: overcoming under- or over-counting errors. Principle of qPAINT method to count the number of proteins of interest. Future directions for quantitative microscopy based on single-molecule fluorescence. Abstract : Quantitative microscopy is needed to understand reactions or phenomena carried out by biological molecules such as enzymes, receptors, and membrane-localized proteins. Counting the biomolecules of interest in single organelles or cellular compartments is critical in these approaches. In this brief perspective, we focus on the development of quantitative fluorescence microscopies that measure the precise copy numbers of proteins in cellular organelles or purified samples. We introduce recent improvements in quantitative microscopies to overcome undercounting or overcounting errors in certain conditions. We conclude by discussing biological applications.